Accuracy assessment of temperature and salinity computed by the 3D Coupled Ecosystem Model of the Baltic Sea (3D CEMBS) in the Southern Baltic. Issue 1 (2nd January 2016) - Nowicki, Artur; Rak, Daniel; Janecki, Maciej; Dzierzbicka-Glowacka, Lidia
ABSTRACT: This paper presents a Coupled Ecosystem Model of the Baltic Sea – 3D CEMBS. The model was developed for the Baltic Sea region and forced by atmospheric data from the UM model (by the Interdisciplinary Centre for Mathematical and Computational Modelling, Warsaw University). The model was compared with hydrological data collected during cruises of r/v 'Oceania'. The analysis covers period from 2010 to 2013 for the main inflow axis on Southern Baltic domain. The evaluation results show a temperature and salinity correlation between the data ca 0.8 and 0.92, respectively. Simulated temperatures and salinity are generally well maintained. However, differences between model and in situ data depend on time and space, and arise with higher gradients.